Tradisi Tahfizh Al-Qur’an di Kampus Pesantren: Studi Living Qur’an di Zona Qur’an Universitas Darussalam Gontor - Muhamad Redho Al Faritzi; Ahmad Qolbi Zidan Johnderose; Muhammad Fajar Hamijar (Fakultas Ushuluddin Adab dan Dakwah IAIN Lhokseumawe, 2025)
The tradition of memorising the Qur'an is one form of active reception by the Muslim community in reviving the Qur'an. At Darussalam Gontor University (UNIDA), this practice is carried out intensively through the Qur'an Zone community under the auspices of Markaz al-Qur'an. This study aims to examine the forms of students' reception of the Qur'an in the daily memorisation tradition in this community. Using a qualitative approach with the Living Qur'an paradigm, data was collected through observation, in-depth interviews, and document analysis. The results show that the tahfizh tradition in the Qur'an Zone is not only a memorisation activity, but also a practice of spiritual and intellectual awareness. The forms of student reception are evident in: (1) the interpretation of memorisation as a form of emotional and intellectual exercise through joint murāja‘ah; (2) collective discipline built through daily schedules, talaqqī, and weekly evaluations; (3) the internalisation of Qur'anic values in academic ethos, such as linking memorisation with time management, perseverance in learning, and self-control; and (4) the strengthening of religious identity through a culture of tadabbur and the habit of additional worship. These findings indicate that the integration of tahfizh in a pesantren-based university environment contributes significantly to the holistic character formation of students, combining spiritual, academic, and social development simultaneously.